Plasma Levels of High-Mobility Group Box 1 during Peptide Vaccination in Patients with Recurrent Ovarian Cancer - Kayoko Waki; Kouichiro Kawano; Naotake Tsuda; Kimio Ushijima; Kyogo Itoh; Akira Yamada (Journal of Immunology Research)
High-mobility group box 1 (HMGB1) is a nuclear protein that is known to be secreted into extracellular fluids from injured cells, activated macrophages, and tumor cells. The clinical correlation of circulating HMGB1 levels with various diseases including cancer has been reported. However, there is no information on HMGB1 levels in cancer patients treated with peptide vaccination. In the present study, we investigated the plasma levels of HMGB1 during personalized peptide vaccination in patients with recurrent ovarian cancer. Frozen plasma samples of 39 patients from previously conducted clinical trials were used in this study. HMGB1 levels were decreased after the 1st cycle of vaccination from their prevaccination levels. However, no correlation was observed between HMGB1 and overall survival (OS). The correlation between plasma HMGB1 levels and other biomarker levels was further analyzed by scatter plot, revealing that HMGB1 levels after the 1st cycle of vaccination were significantly correlated with myeloid-derived suppressor cell (MDSC) frequency after the 1st cycle of vaccination (r=0.357, p=0.032). Chi-square test showed that epitope spreading was significantly related with changes of HMGB1 (p=0.030). These results suggest that plasma HMGB1 is a possible biomarker for cancer vaccine therapy, although direct correlation with OS has not been obtained. This trial is registered with Clinical Trial Registry under trial numbers UMIN000003083 and UMIN000001482.